Effectiveness of ultrasound addition in intervention McKenzie’s neck exercise in reducing the mechanical neck pain - Widi Arti; Andi Fadhilah Tenriwulan; Bagas Anjasmara (Universitas Udayana dan Diaspora Taipei Medical University, 2023)
Background: The activity of using a smartphone for a long time in a static position and bad posture, will result in Mechanical neck pain (MNP), which is known as a neck condition caused by change in the cervical curve to flatten due to overload on the muscles, ligaments, joints, and bones of the neck at the back and the muscles of the upper back and shoulders. The effectiveness of adding ultrasound to the McKenzie’s neck exercise (MNE) intervention to reduce MNP. Methods: The study used a quasi-experimental method with a pre and post-two-group design. The number of samples was 20 research subjects experiencing chronic non-specific MNP, not experiencing spondylolisthesis, fracture, and hernia nucleus pulposus in the cervical area. Group I was given the MNE and ultrasound, and group II was give MNE only. This research was conducted three times a week for four weeks at the Action and Hydrotherapy Laboratory. The measuring tool used is the northwick neck pain tool. Normality test using Shapiro Wilk test and homogeneity test using Lavene's test. Paired sample t-test was used to determine the effectiveness of the intervention of the two groups in reducing MNP, and an independent sample t-test was to see the difference in the effect of the intervention results of the two groups. Results: The characteristics of study respondents by age were in the average range of 19.7±0.9 years for group I and 19.6±0.6 years for group II. Based on other data, groups I and II decreased pain significantly after their respective treatments (p =0.04). There is no significant difference effect after interventions between the group I and group II (p >0.05). Conclusions: The program of MNE only effectively reduced MNP with the same good effect as the MNE with ultrasound therapy in subject with MNE. The addition of ultrasound to the MNE does not have a significant effect on pain reduction.